Current issues of using the coastal areas of the Baltic sea : (the example of Russia and Poland) - Anisimov, Aleksey (Array, 2021)
The article proves that the existing threats to coastal marine areas that are notable for significant vulnerability to human activity require changes in Russian water legislation, which must introduce the category “coastal territories” and clarify the regime of permissions, restrictions and prohibitions within them. This will make it possible to more effectively regulate the economic, environmental and social aspects of the use and protection of the marine environment and coastal areas. For Russian water law, a number of legal structures that are successfully used in Polish water law are of interest, including the allocation of two zones with special legal regime on the coast, environmental planning of the use and protection of the coast and sea waters, as well as a set of measures to ensure sustainable development of coastal areas.